Perempuan dan pemaknaan triple bottom line di kawasan mangrove surabaya - Widyaningrum, Anastasia Yuni; Nugraheni, Yuli (Jurnal Studi Komunikasi, 2019)
Mangrove area identically are slum because they are located in river estuaries with unplanned environmental management. Not so with the mangrove area at Gunung Anyar Tambak Surabaya. Women in this region actively carry out nature conservation and protect the environment so that they are well preserved. This research was conducted with the aim to find out how women interpret the triple bottom line concept as a pillar of Corporate Social Responsibility implemented by the National Electricity Company of East Java. Data was collected by FGD, interviews and also environmental observations. Phenomenology as a theory and also the method used in this study. Triple bottom line concept and Corporate Social Responsibility are used to analyse. The results of the study show that the meaning of women about the triple bottom line concept is a part of their daily lives that cannot be separated. The existence and absence of a Corporate Social Responsibility program from the National Electricity Company will make women in the mangrove area of Gunung Anyar Tambak continue to carry out environmental hygiene from garbage flowing in the river. Thus the triple bottom line pillar, namely planet (natural environment) is maintained and benefits profit (profit, second pillar) and this is an active awareness (people, third pillar) of women in the mangrove area of Gunung Anyar Tambak Surabaya.